Molecular characterization of florfenicol and oxazolidinone resistance in Enterococcus isolates from animals in China - Li, Pingping; Gao, Mengdi; Feng, Chunlin; Yan, Tielun; Sheng, Zhiqiong; Shi, Weina; Liu, Shuang; Zhang, Lei; Li, Anqi; Lu, Junwan; Lin, Xi; Li, Kewei; et al. (Frontiers in Microbiology, 2022)
Florfenicol is widely used for the treatment of bacterial infection in domestic animals. The aim of this study was to analyze the molecular mechanisms of florfenicol and oxazolidinone resistance in Enterococcus isolates from anal feces of domestic animals. The minimum inhibitory concentration (MIC) levels were determined by the agar dilution method. Polymerase chain reaction (PCR) was performed to analyze the distribution of the resistance genes. Whole-genome sequencing and comparative plasmid analysis was conducted to analyze the resistance gene environment. A total of 351 nonduplicated enteric strains were obtained. Among these isolates, 22 Enterococcus isolates, including 19 E. faecium and 3 E. faecalis were further studied. 31 florfenicol resistance genes (13 fexA, 3 fexB, 12 optrA and 3 poxtA genes) were identified in 15 of the 19 E. faecium isolates, and no florfenicol or oxazolidinone resistance genes were identified in 3 E. faecalis isolates. Whole-genome sequencing of E. faecium P47 which had all four florfenicol and oxazolidinone resistance genes and high MIC levels for both florfenicol (256 mg/L) and linezolid (8 mg/L), revealed that it contained a chromosome and 3 plasmids (pP47-27, pP47-61 and pP47-180). The four florfenicol and oxazolidinone resistance genes were all related to the insertion sequences IS1216 and located on two smaller plasmids. The genes fexB and poxtA encoded in pP47-27, while fexA and optrA encoded in the conjugative plasmid pP47-61. Comparative analysis of homologous plasmids revealed that the sequences with high identities were plasmid sequences from various Enterococcus species except for the Tn6349 sequence from a Staphylococcus aureus chromosome (MH746818.1). The current study revealed that florfenicol and oxazolidinone resistance genes (fexA, fexB, poxtA and optrA) were widely distributed in Enterococcus isolates from animal in China. The mobile genetic elements, including the insertion sequences and conjugative plasmid played an important role in the horizontal transfer of florfenicol and oxazolidinone resistance.